Improving the connectivity resilience of a telecommunications network to multiple link failures through a third-party network - Sousa, Amaro de (2020)
Currently, telecommunication networks are fully resilient, in terms of connectivity, to single link failures. On the other hand, multiple simultaneous link failures are becoming a concern to network operators, mainly due to malicious human activities. Full connectivity resilience to multiple link failures is too costly and other solutions must be envisaged. For a given maximum number of simultaneous link failures, the connectivity resilience metric adopted here is the minimum number of network node pairs that can still communicate for any set of failing links. In this work, the connectivity resilience to multiple link failures is improved by resorting to a third-party network for temporary additional connectivity (i.e., while the failing links are not reestablished). In such a solution, some nodes must be selected to act as gateway nodes between the two networks. For a given network topology and a given number of gateway nodes, the aim is to select the most appropriate gateway nodes so that the connectivity resilience is improved as much as possible. To address this problem, a Gateway Node Selection (GNS) algorithm is proposed where the most damaging sets of failing links are identified and, then, a set cover problem type is defined and solved to select the gateway nodes. The computational results demonstrate the effectiveness of the proposed GNS algorithm over two well-known network topologies.